Phospholipases and the Network of Auxin Signal Transduction with ABP1 and TIR1 as Two Receptors: A Comprehensive and Provocative Model - Scherer, Günther F.; Labusch, Corinna; Effendi, Yunus (Frontiers in Plant Science, 2012)
Phospholipase D (PLD), secreted phospholipase A2 (sPLA2) and patatin-related phospholipase A (pPLA) are important elements in auxin signal transduction. PLDζ2 has a function in auxin transport. PLD's potential link to upstream receptors ABP1 or TIR1, and to cytosolic calcium as an activator of PLDζ2, is outlined. A link from PLDζ2 to activation of PINOID, a kinase activating PIN proteins, is suggested. The activation mechanism of sPLA2, also involved in auxin transport-related functions, is unknown. New experiments show that not only ABP1 but also pPLA isoforms are tied to rapid activation of early auxin-induced genes, the functional domain of the other auxin receptor TIR1. Post-translational activation mechanisms for pPLAs are suggested to be tied to ABP1. We propose pPLAs and PLDζ2 are mediators in auxin signaling. The downstream targets of regulation by ABP1 as the receptor we propose to be primarily PIN proteins. This coordinates gene expression regulation by TIR1 in the nucleus. A clear separation of cytosolic mechanisms of auxin signalling is suggested with ABP1 as receptor, and phospholipases A and D and PIN proteins as downstream targets on the on hand, and TIR1 and regulation of early auxin-induced genes on the other. At the same time, this separation is coordinated by auxin transport creating the auxin concentration in the nucleus suitable for gene regulation.